Effect of pre-treatment with rocuronium and vecuronium on post succinylcholine fasciculations, serum potassium, and postoperative myalgia: A prospective, randomized, double-blind study - Dilip Kothari; Sonali Tripathi; Ritesh Upadhyay (Asian Journal of Medical Sciences, 2022)
Background: Succinylcholine with quick onset, ultra short duration of action, and complete predictable paralysis has been the best drug for endotracheal intubation but the occurrence of side effects such as muscle fasciculations, postoperative myalgia, rise in serum potassium levels and myoglobinuria limits its use in the full stomach, burns, massive trauma, metabolic acidosis, and few myopathies. For attenuation of these effects, many drugs have been studied but pre-treatment with non-depolarizing muscle relaxant found to be successful.